A qualitative exploration of the salience of MTV-Shuga, an edutainment programme, and adolescents' engagement with sexual and reproductive health information in rural KwaZulu-Natal, South Africa. Issue 1 (31st December 2022) - Kyegombe, Nambusi; Zuma, Thembelihle; Hlongwane, Siphesihle; Nhlenyama, Mxolisi; Chimbindi, Natsayi; Birdthistle, Isolde; Floyd, Sian; Seeley, Janet; Shahmanesh, Maryam
Abstract: Young people, particularly adolescent girls and young women, represent a growing proportion of those living with HIV. Edutainment programmes have been widely used throughout the world to "educate" and "entertain" audiences and tackle serious social issues in bold and engaging ways. This paper examines the extent to which an edutainment programme, MTV-Shuga, was reported to influence young people's engagement with sexual and reproductive health (SRH) information in rural KwaZulu-Natal, South Africa. In 2019 we conducted eight community-based screenings of MTV-Shuga episodes followed by 25 individual in-depth interviews and 13 focus group discussions with young people aged between 15 and 30. Interviews were audio recorded and transcribed verbatim. Data analysis was thematic and complemented by constant comparison and deviant case analysis techniques. In this rural and poor setting with a high burden of HIV, young people exhibited high levels of awareness of SRH and HIV but had constrained access to services, and limited ability to engage with parents or guardians on SRH matters. MTV Shuga provided an entertaining guide of ways to navigate the risks that they faced in a way that resonated with them. The findings highlight the importance of enabling young people in rural areas to watch MTV Shuga with peers in a safe space in which discussion of the content is facilitated. There is also value in encouraging parents to watch MTV Shuga as a means of enabling discussions between children and adults in their lives about SRH matters.